The Community Aspect of Kant’s Virtuous Circle Between Ethics and Politics - Martinazzo, Nicole (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article examines the interplay between the moral and the political in Kant’s thought theconcept of community. In doing so, it draws an analogy between two relations: that between the ethical andthe political community, and that between moral and political progress. Through this analogy, I argue (i) thatKant grants logical precedence to political progress, (ii) that there is a virtuous circle between moral andpolitical progress, and (iii) that forming a community is both a duty and a human predisposition.